Access granted: Facebook's free basics in Africa. (April 2020) - Nothias, Toussaint
This article explores one of the most notorious and controversial initiatives by tech corporations to increase connectivity across the Global South: Facebook's Free Basics project. Public attention focused on its ban in India following nationwide protests about net neutrality. In Africa, however, Free Basics expanded without much public scrutiny to some 32 countries. This article traces this quiet expansion by using an innovative virtual private network (VPN)-based method and by calling for an analytical focus on the landscape of the digital civil society in Africa. Specifically, I outline two key, interrelated phenomena: (1) Facebook's evolving strategy, including a greater engagement with civil society organizations and (2) the focus of digital rights activists in Africa on issues like Internet shutdowns, government surveillance, and the lack of data privacy frameworks. In the process, I illuminate broader trends in the digital industry including tech corporations' growing investments in mobile social media, network infrastructures, and in civil society; the use of disadvantaged populations and unregulated territories for digital experiments and data extraction; and the mounting recognition of Facebook's political role, both within and outside the corporation.